ENHANCED ENZYMATIC ACTIVITY OF STREPTOMYCES GRISEOPLANUS L-ASPARGINASE VIA ITS INCORPORATION IN AN OIL-BASED NANOCARRIER - EL-HADI, ABEER A.; AHMED, HANAN MOSTAFA; ZAKI, RANIA A.; MOHSEN, AMIRA MOHAMED (International Journal of Applied Pharmaceutics, 2020)
Objective: L-asparaginase (L-asp) is a vital enzyme used as a therapeutic agent in combination with other drugs in the treatment of acute lymphoma, melanosarcoma and lymphocytic leukemia. Immobilization of enzymes through loading on nanoemulsion (NE) results in some advantages such as enhancing their stability and increasing their resistance to proteases. Aim of the present study is to formulate L-asp loaded nanoemulsion to enhance its efficiency and thermal stability. Methods: Nanoemulsion loaded with L-asp crude extract (specific activity 13.23U/mg protein) was prepared employing oleic acid as oil, tween 20/tween 80 as surfactants and propylene glycol (PG) as co-surfactant. L-asp loaded NE underwent several thermodynamic stability studies and the optimized formulae were further examined for their biochemical properties and thermal stability. Results The developed formulations were spherical in shape and their sizes were in the nanometric dimensions with negatively charged zeta potential values. Upon comparing the enzyme activity of L-asp loaded NE employing tween 20 (F1) or tween80 (F4) at different concentrations, the results revealed that F4 NE showed higher enzymatic activity [323 U/ml] compared to F1 NE [197 U/ml] at the same concentration. The nanosized immobilized L-asp was more stable in the pH range from 8 to 8.5 as compared to free L-asp. The immobilized enzyme preserved about 59.11% of its residual activity at 50 °C; while free L-asp preserved about 33.84%. Conclusion: In the view of these results, NE composed of oleic acid, tween 80 and PG represents a promising dosage form for enhancing the activity and stability of Streptomyces griseoplanus L-asp.